KATP Channels Mediate Differential Metabolic Responses to Glucose Shortage of the Dorsomedial and Ventrolateral Oscillators in the Central Clock - Jyh-Jeen Yang (Nature Portfolio, 2017)
Abstract The suprachiasmatic nucleus (SCN) central clock comprises two coupled oscillators, with light entraining the retinorecipient vasoactive intestinal peptide (VIP)-positive ventrolateral oscillator, which then entrains the arginine vasopressin (AVP)-positive dorsomedial oscillator. While glucose availability is known to alter photic entrainment, it is unclear how the SCN neurones respond to metabolic regulation and whether the two oscillators respond differently. Here we show that the ATP-sensitive K+ (KATP) channel mediates differential responses to glucose shortage of the two oscillators. RT-PCR and electrophysiological results suggested the presence of Kir6.2/SUR1 KATP channels in the SCN neurones. Immunostaining revealed preferential distribution of Kir6.2 in the dorsomedial subregion and selective colocalization with AVP. Whole cell recordings with ATP-free pipette solution indicated larger tolbutamide-induced depolarisation and tolbutamide-sensitive conductance in dorsal SCN (dSCN) than ventral SCN (vSCN) neurones. Tolbutamide-sensitive conductance was low under perforated patch conditions but markedly enhanced by cyanide inhibition of mitochondrial respiration. Glucoprivation produced a larger steady-state inhibition in dSCN than vSCN neurones, and importantly hypoglycemia via opening KATP channels selectively inhibited the KATP-expressing neurones. Our results suggest that the AVP-SCN oscillator may act as a glucose sensor to respond to glucose shortage while sparing the VIP-SCN oscillator to remain in synch with external light-dark cycle.